Cause Analysis of Colored Smoke Plume and Related Studies on Economic and Environmental Benefits of Its Treatment Technologies for Ultra-low Emission Coal-Fired Power Plants - Fahua ZHU; Zunqiang SUN; Zhiyong SHEN (Zhongguo dianli)
The definition and causes of various colored smoke plume are introduced systematically in this paper. Colored smoke plume should be treated according to not only its exact causes but also the environmental and policy requirements. White smoke plume is commonly seen in ultra-low emission coal-fired power plants, while blue smoke plume appears in a small number of power plants burning medium and high sulfur coal. The article explores the treatment technologies, investment, operating costs as well as their economic and environmental benefits with the focus on blue smoke plume and white smoke plume. It turns out that the pollutant emission reduction and water-saving benefit from the treatment of white smoke plume are very limited, or it may even get worse by increasing the emission of pollutants. Therefore, it is not recommended to be widely promoted. For the treatment of blue smoke plume, it is necessary to strengthen the research and demonstration project of SO3 detection and treatment technologies for flue gas, and publish the emission standards of SO3 to make the treatment of the blue smoke plume in power plant follow the standard guidelines.